2011 IEEE International Symposium of Circuits and Systems (ISCAS) 2011
DOI: 10.1109/iscas.2011.5937652
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of time-multiplexed sparse periodic FIR filters for FRM on FPGAs

Abstract: Abstract-Frequency-response masking (FRM) is a set of techniques for lowering the computational complexity of narrow transition band FIR filters. These FRM use a combination of sparse periodic filters and non-sparse filters. In this work we consider the implementation of these filters in a time-multiplexed manner on FPGAs. It is shown that the proposed architectures produce lower complexity realizations compared to the vendor provided IP blocks, which do not take the sparseness into consideration. The designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This work extends the previous work of the authors as reported in [9]. We proposed an architecture for time-multiplexed periodic model filters and showed it to achieve low resource utilization when compared to vendor provided time-multiplexed FIR cores because these cores were not able to fully utilize the sparsity.…”
Section: Design Methodologysupporting
confidence: 53%
See 4 more Smart Citations
“…This work extends the previous work of the authors as reported in [9]. We proposed an architecture for time-multiplexed periodic model filters and showed it to achieve low resource utilization when compared to vendor provided time-multiplexed FIR cores because these cores were not able to fully utilize the sparsity.…”
Section: Design Methodologysupporting
confidence: 53%
“…We proposed an architecture for time-multiplexed periodic model filters and showed it to achieve low resource utilization when compared to vendor provided time-multiplexed FIR cores because these cores were not able to fully utilize the sparsity. In [9], two architectures were proposed: a non-pipelined and a pipelined one, along with an adjustment for odd filter length. For brevity, we will only describe the pipelined architecture for odd filter lengths.…”
Section: Design Methodologymentioning
confidence: 99%
See 3 more Smart Citations